Treatment device for neonatal birth asphyxia related Hypoxic Ischemic Encephalopathy - Rediet Zewdie; Lidet Getachew; Geremew Dubele; Ababo Oluma; Gedion Israel; Kokeb Dese; Gizeaddis Lamesgin Simegn (BMC, 2021)
Abstract Background Birth asphyxia is a leading cause of neonatal brain injury, morbidity, and mortality globally. It leads to a multi-organ dysfunction in the neonate and to a neurological dysfunction called Hypoxic Ischemic Encephalopathy (HIE). Cooling therapy is commonly used to slow or stop the damaging effects of birth asphyxia. However, most of the cooling devices used in the healthcare facility do not have a rewarming functionality after cooling therapy. A separate rewarming device, usually a radiant warmer or incubator is used to rewarm the infant after therapy, causing additional burden to the healthcare system and infant families. The objective of this project was, therefore, to design and develop a cost-effective and efficient total body cooling and rewarming device. Methods Our design includes two water reservoirs that operate by pumping cold and warm sterile water to a mattress. After decreasing the infant's core body temperature to 33.5 °C, the system is designed to maintain it for 72 h. Feedback for temperature regulation is provided by the rectal and mattress temperature sensors. Once the cooling therapy is completed, the system again rewarms the water inside the mattress and gradually increases the neonate temperature to 36.5-37 °C. The water temperature sensors' effectiveness was evaluated by adding 1000 ml of water to the reservoir and cooling and warming to the required level of temperature using Peltier. Then a digital thermometer was used as a gold standard to compare with the sensor's readings. This was performed for five iterations. Results The prototype was built and gone through different tests and iterations. The proposed device was tested for accuracy, cost-effectiveness and easy to use. Ninety-three point two percent accuracy has been achieved for temperature sensor measurement, and the prototype was built only with a component cost of less than 200 USD. This is excluding design, manufacturing, and other costs. Conclusion A device that can monitor and regulate the neonate core body temperature at the neuroprotective range is designed and developed. This is achieved by continuous monitoring and regulation of the water reservoirs, mattress, and rectal temperatures. The device also allows continuous monitoring of the infant's body temperature, mattress temperature, reservoir temperature, and pulse rate. The proposed device has the potential to play a significant role in reducing neonatal brain injury and death due to HIE, especially in low resource settings, where the expertise and the means are scarce.